Adaptation of Malt Barley (Hordeum Vulgare L.) Varieties in the highlands of North Gondar - Tahir, Zeynu; Azanaw, Asfaw (ABC Journal of Advanced Research, 2019)
Study was initiated with the objectives to identify high yielder malt barley varieties. The trial has been conducted during 2014 main season and laid out on randomized complete block design with three replications. Analysis of variance was computed using SAS, 2002. At Dabat, result showed that highly significant difference among the varieties (p < 0.05) for all agronomic traits. At Debark and Wegera the analysis of variance indicated that highly significant to a significant difference among varieties at p < 0.05 for days to heading, days to maturity, plant height, spike length, thousand seed weight and grain yield, and seed per spike. The combined analysis of variance showed that highly significant difference among varieties for days to heading, days to maturity, plant height, spike length, and grain yield. The location also contributed the significant effect for all yield components except biomass and grain yield. The interaction of location by genotype showed the highly significant difference on days to maturity and plant height. The average heading days ranged from 70-81 and the average maturity days were ranged from 127-136. Among the tested varieties, IBON-174/03 and SABINI exhibited highest grain yield. The overall combined analysis indicated that IBON-174/03 and SABINI were high yielder and well adapted at the tested sites. Therefore those varieties are recommended for production in the testes sites, and similar agro-ecologies.